A study on the status of the libraries in the first and second legislative districts of Leyte - Ortego, Shauntel P.; Santos, Yhna Therese P. (Quezon City School of Library and Information Studies, University of the Philippines, 2016)
Concerning the theses submitted to the UP SLIS, it is evident that studies regarding libraries in the localities and in the outlying barrios in the southern part of the Philippines have been rarely conducted. There is a lack of information regarding the current situation of the libraries in the other provinces of the Philippines, most importantly in the in the Visayas and Mindanao. It is along this vein that this study was conducted. Due to time and financial constraints, this s tudy was limited to the libraries (regardless of type) in the 1st and 2nd legislative districts of Leyte. It is worth noting that the said districts were also among the hardly-hit areas during the onslaught of Typhoon Yolanda. Specificaly, this study sought to determine the status of the 49 libraries surveyed in terms of a) administration; b) collection; c) services; d) budget; e) staff; and f) physical space and facilities. The respective head librarians or the library administrators of these libraries were asked to answer a questionnaire. In the absence of either of these two, a library staff knowledgeable about the library programs and operations served as the respondent. The study revealed that only 19 out of 49 libraries surveyed or 38.78% are managed by full-time professional librarians. Most of the libraries have weak print and non-print collections. In fact, only 6 of 12 academic libraries (50%) and 9 of 21 school libraries (42.68%) have met the minimum number requirement for core book collection as set forth in the Standards for Philippine Libraries (SPL). In addition, it was also revealed that majority of the libraries lack the implementation of the security and control measures listed in the SPL such as the provision of emergency exits and emergency lights, implementation of security system, and so on. Moreover, it was also found that a relative large number of libraries still experience budgetary constraints, which directly affect their efforts to enhance the current state of their libraries, especially in terms of collections, facilities, equipment and services. Based on these salient findings, although the conditions of the libraries surveyed vary from each other, it is evident that there are still a number of concerns that should be addressed with regard to the development of these libraries. These include the weak print and non-print collections as well as the inadequacy of library furniture and equipment. There is also a lack of competent library professionals to manage most of the libraries. Moreover, financial constraints also seem to be restraining the development of these libraries.
Thesis (Bachelor of Library and Information Science)--University of the Philippines Diliman
Keywords: Academic libraries -- Philippines -- Leyte; School libraries -- Philippines -- Leyte